2018
DOI: 10.1080/21620555.2018.1430509
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Early Occupational Attainment: The Roles of Study Field, Gender Norms, and Gender Attitudes

Abstract: Based on the data from the Beijing College Student Panel Survey (BCSPS), this paper examines the effect of study fields on gender disparities in early occupational achievement. Multinomial logistic regression suggests that field of study can only explain part of the occupational gender differences. Women are more likely than men to become office clerks-a typical female occupation even if the field of study is controlled. Relative to clerks, gender disparities in entry into professional and technicians (male-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 72 publications
3
37
0
Order By: Relevance
“…Furthermore, the results from both samples indicated that gender and STEM self-efficacy were the two most salient variables in our prediction models, which were in accordance with previous studies (Mau et al, 1995;Twenge & Campbell, 2018;Wang, 2012). The current findings are generally consistent with other studies focused on gender difference within culturally and ethnically diverse samples (He & Zhou, 2018;Kermani & Aldemir, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the results from both samples indicated that gender and STEM self-efficacy were the two most salient variables in our prediction models, which were in accordance with previous studies (Mau et al, 1995;Twenge & Campbell, 2018;Wang, 2012). The current findings are generally consistent with other studies focused on gender difference within culturally and ethnically diverse samples (He & Zhou, 2018;Kermani & Aldemir, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Findings from this study added to the growing body of empirical literature on gender difference regarding parental involvement, learning experience, and self-efficacy, and STEM career aspiration. In accordance with previous research (He & Zhou, 2018;Ing, 2014;Mau et al, 2019;Mau & Li, 2018;Wang & Degol, 2013), the present study provides additional evidence that gender differences in STEM career interests remain pervasive among high school students. Male students were more likely to participate in the STEM workforce than female students regardless of the socio-cultural contexts.…”
Section: Discussionsupporting
confidence: 92%
“…As women are responsible for a greater share of domestic work than men, especially when they have young children to care for, they are seen as being less committed to the workplace and more likely to quit jobs for family reasons (Cha 2010(Cha , 2013Jacobs 1989;Kan and He 2018;Marini 1989;Stone 2007;Treiman and Hartmann 1981). If employed, they are more likely to remain in lower-paid occupations traditionally dominated by women (e.g., He and Wu 2019;He and Zhou 2018;Levanon and Grusky 2016;Marini 1989). Hence, it is women's family role that holds off their career advancement in the labor markets.…”
Section: Family Work and Women's Career Contingency: A Two-sphere Separation Perspectivementioning
confidence: 99%
“…To facilitate sampling, the BCSPS took advantage of the registration cards for all of the students who were enrolled in 2009 as the sampling frame and adopted the proportional‐to‐population sampling strategy. The primary sampling units were higher education institutions, from which the secondary sampling units were fields of study (see Cai & Wang, ; He & Zhou, ; Li & Feng, 2018; X. G. Wu, ; D. Xu, ; Wu, Li, & Wang, in press).…”
Section: Empirical Strategiesmentioning
confidence: 99%